From research to bedside: Incorporation of a CGA‐based frailty index among multiple comanagement services. Issue 1 (13th September 2021) - Cooper, Lisa; Loewenthal, Julia; Frain, Laura N.; Tulebaev, Samir; Cardin, Kristin; Hshieh, Tammy T.; Dumontier, Clark; Streiter, Shoshana; Joseph, Carly; Hilt, Austin; Theou, Olga; Rockwood, Kenneth; et al.
Abstract: The comprehensive geriatric assessment (CGA) is the core tool used by geriatricians across diverse clinical settings to identify vulnerabilities and estimate physiologic reserve in older adults. In this paper, we demonstrate the iterative process at our institution to identify and develop a feasible, acceptable, and sustainable bedside CGA‐based frailty index tool (FI‐CGA) that not only quantifies and grades frailty but also provides a uniform way to efficiently communicate complex geriatric concepts such as reserve and vulnerability with other teams. We describe our incorporation of the FI‐CGA into the electronic health record (EHR) and dissemination among clinical services. We demonstrate that an increasing number of patients have documented FI‐CGA in their initial assessment from 2018 to 2020, while additional comanagement services were established (Figure 2). The acceptability and sustainability of the FI‐CGA, and its routine use by geriatricians in our division, were demonstrated by a survey where the majority of clinicians report using the FI‐CGA when assessing a new patient and that the FI‐CGA informs their clinical management. Finally, we demonstrate how we refined and updated the FI‐CGA, we provide examples of applications of the FI‐CGA across the institution and describe areas of ongoing process improvement and challenges for the use of this tailored yet standardized tool across diverse inpatient and outpatient services. The process outlined can be used by other geriatric departments to introduce and incorporate an FI‐CGA. Abstract : See related editorial by Callahan in this issue.